Incidence, Magnitude, and Predictors of Shortening in Young Femoral Neck Fractures. Issue 9 (September 2015) - Stockton, David J.; Lefaivre, Kelly A.; Deakin, Daniel E.; Osterhoff, Georg; Yamada, Andrew; Broekhuyse, Henry M.; O'Brien, Peter J.; Slobogean, Gerard P.
Abstract : Objectives: To describe the incidence and magnitude of femoral neck fracture shortening in patients age younger than 60 years. Secondarily, to examine predictors of fracture shortening. Design: Retrospective chart review. Setting: Level I trauma centre. Patients/Participants: Sixty-five patients with a median age of 51 years (interquartile range: 42–56 years) were included. Seventy-one percent were male, 75% were displaced fractures, and 78% were treated with cancellous screws. Intervention: Internal fixation with multiple cancellous screws or sliding hip screw (SHS) + derotation screw. Main Outcome Measurements: Radiographic femoral neck shortening at a minimum of 6 weeks after fixation. Results: Fifty-four percent of patients had ≥5 mm of femoral neck shortening (22% had between ≥5 and <10 mm and 32% ≥10 mm). Initially, displaced fractures shortened more than undisplaced fractures (mean: 8.1 vs. 2.2 mm, P < 0.001), and fractures treated with SHS + derotation screw shortened more than fractures with cancellous screws alone (10.7 vs. 5.5 mm, P = 0.03). Even when adjusting for initial fracture displacement, fractures treated with SHS + derotation screw shortened an average of 2.2 mm more than fractures treated with screws alone ( P = 0.03). Conclusions: The incidence of clinically significant shortening in our young femoral neck fracture population was higher than anticipated, and 32% of patients experienced severe shortening of >1 cm. Our findings highlight the need for further research to determine the impact of severe shortening on functional outcome and to determine if implant selection affects fracture shortening. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.